STRUCTURE OF RUSSIAN PUBLICATIONS IN CLINICAL IMMUNOLOGY AND ALLERGOLOGY (JOURNAL ARTICLES, CLINICAL TRIALS, META-ANALYSES AND PRACTICE GUIDELINES) IN COMPARISON WITH OTHER BRICS COUNTRIES IN 2008-2015 - L. I. Lugacheva; M. I. Musatov (Медицинская иммунология, 2018)
It is obvious that any evolving scientific medical field is a dynamic system that cannot stay at the stage of accumulation of primary information, and inevitably goes to the stages of clinical trials, generalization of information in meta-analyses and completes the study by creation of practical guidelines. The purpose of this study was a quantitative analysis of publicly available data in the field of clinical immunology in Russia during 2008-2015, identifying the ratios of clinical trials, meta-analyses, and practical guidelines, as well as evaluating the results by comparison with other BRICS countries. Study design was performed by retrospective bibliometric methods. It is revealed, that, in Russia, 16 clinical trials, 3 meta-analyses and 1 practice guideline were issued per 1000 original journal articles. Accordingly in the People’s Republic of China this ratios have made 34/25/4; in Federal Republic of Brazil, 42/87/7; in Republic of India, 76/58/34, and in Republic of Southern Africa, 134/43/36. Moreover, we have obtained evidence which suggests optimistic prospectives for scientific clinical immunology in Russia.